Arterial supply of the stomach of the Egyptian native goat - Mohamed, Reda; Adam, Zein; Gad, Mohamed (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This study was conducted to investigate the origin, course and distribution of the arteries supplying the stomach of the goat which is of extreme clinical importance for surgeon during caprine rumenotomy. Materials and methods: Fifteen adult goats were used in this study to demonstrate the arterial supply of the stomach by injection of the thoracic aorta with red gum milk latex after general anesthesia and slaughtering of the animals. Gross dissection of the arteries of the stomach was done to detect the origin, course and distribution of these arteries. Results: The study revealed that the rumen was richly supplied by the right and left ruminal arteries as well as ruminal branches from the reticular artery. The reticulum was supplied with reticular branches of reticular and accessory reticular arteries. The omasum was vascularized by omasal branches of the left gastric artery. While the abomasum received its entire arterial supply from abomasal branches of the left gastric, left gastroepiploic, right gastric and right gastroepiploic arteries. Conclusion: The stomach of the goat receives its arterial supply from the branches of the right ruminal, left ruminal, reticular, left gastric and hepatic arteries. Rumenotomy could be done in the left aspect of the dorsal ruminal sac, between the area of anastomoses of the terminal branches of the left and right ruminal arteries as the blood supply was minimal, so that bleeding will be low. http://doi.org/10.5455/javar.2017.d194